Penanganan Pembiayaan Murabahah Macet Pada Koperasi Pondok Pesantren (KOPONTREN) XYZ - Sunarno Sunarno; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Murabaha Financing have potentially lower risk than other financing product. It chosen by USP Kopontren XYZ to fulfill members financing demand both for business development and consumptive purposes. Termination of Employment Relationship, working cycle and Bad characters some members cause of the collectibility default in Murabaha Financing.This study using qualitative approach and case studies. The collection of primarydata through in-depth interview, while secondary data obtained from the AnnualMembers Meeting report Kopontren XYZ . Explanation building analysis techniques are use to explain the results of in-depth interviews in order to explain the handling of murabaha financing collectibility default.The results explained to handling collectability default adopt according to The Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 35.3 / Per / M.KUKM / X / 2007, executing from cash collateral, financial penalties for those who deliberately, and converts the contract.